The Role of Educational Institutions in the Civilizations of Iraq, Ancient and Modern - Hussein, Prof.Dr. Ghosoun Mazhar Hussein; Abde, Dr. Mahmoud Saleh Abdel (Sulaimani Journal for Humanities, 2026)
This research seeks to shed light on the pivotal role played by educational institutions in shaping the civilizational features of any country throughout history. Education is considered a major foundation in the development and prosperity of nations, as the development of any country is measured by the level and quality of its educational system. Through education, societies rise to the highest levels of sophistication and civilizational giving. The importance of this research lies in reviewing the historical role and gradual development of educational institutions in Iraq from ancient times to the modern era. The research begins by reviewing the emergence of the Kuttabs, where children learned to read and write, through the emergence of religious schools, then the matter developed with the emergence of missionary schools under the auspices of European countries. Over time, Iraq witnessed the establishment of official schools and universities that contributed to building an integrated educational system.
Keywords: educational institutions; Iraqi civilizations; ancient times; modern times